A Review Paper On - Analysis And Performance Evaluation For Congestion Control Routing Protocols In Manet - Ahlawat, Bhawna; Nandal, Vikas (International Journal of Computer Sciences and Engineering, 2018)
MANET is aggregation of wireless mobile nodes that can transmit in absence of main controller and do not have fixed configuration. MANET has dynamic nature due to which every node travel effortlessly in network. The multipaths has to be constructed in order to avoid and control congestion. In MANET, link collapse or node failure could be a reason for packet loss. There are many problems and outcomes in mobile ad-hoc network. Presence of many nodes transmitting packets simultaneously over network, the probability of mislaying packet over the network advances to a larger scope. Various congestion control techniques and algorithms has been discussed in this paper. The motive of the paper is to examine and contrast among many proposed techniques of congestion control in MANETs.